Hubungan Bauran Pemasaran Dengan Loyalitas Pasien Poliklinik Instalasi Rawat Jalan di RSUD Nyi Ageng Serang Kulon Progo: The Relationship between Mix Marketing with Patient Loyality in Outpatient Service at General Hospital of Nyi Ageng Serang Regency, Kulong Progo - Mudayana, Ahmad Ahid; Nurbaiti Rahmah (International Journal of Healthcare Research, 2023)
Background:  The marketing mix is a solution for patient problems, in obtaining pleasant, comfortable service and good communication from the hospital to customers. Loyalty level that displays the need to have a high sense of loyalty, as well as having a beneficial effect on the healthcare organization. The purpose of this study was to determine the relationship between the marketing mix and patient loyalty in the outpatient installation polyclinic at the Nyi Ageng Serang Kulon Progo Regional General Hospital. Methods: This research is a quantitative research approach cross-sectional. The sample in this study was 110 outpatient polyclinic patients selected by purposive sampling. There search was conducted in June-July 2023 at Nyi Ageng Serang Hospital, Kulon Progo. Data analysis univariate, bivariate and multivariate with Chi Square statistical tests and Multiple Linear Regression statistical tests. Results: The study showed that marketing mix in this hospital could be classified sufficient for product and physical dimension, good for price and promotion, and bad for location, human resource, and process. Conclusion:  This study concludes that the marketing mix of hospitals in RSUD Nyi Ageng Serang, Kulon Progo for product and physical dimensions is quite sufficient, price and promotion dimensions are good, while for place, people, and process are not good. Therefore, the Hospital, especially the Public Relations and Marketing unit, can optimize various marketing innovations to patients, families, and the community.